Nucleation at solid–liquid interfaces is accompanied by the reconfiguration of electrical double layers - Qian Ai; Lalith Krishna Samanth Bonagiri; Kaustubh S. Panse; Jaehyeon Kim; Shan Zhou; Yingjie Zhang (Proceedings of the National Academy of Sciences, 2025)
In electrochemical systems, the structure of electrical double layers (EDLs) near electrode surfaces is crucial for energy conversion and storage functions. While the electrodes in real-world systems are usually heterogeneous, to date the investigation of EDLs is mainly limited to planar, homogeneous substrates. To bridge this gap, here we image the EDL structure of an ionic liquid/graphite battery anode system in the initial stage of interfacial nucleation and growth using our recently developed electrochemical 3D atomic force microscopy. Upon surface nucleation of lithium-containing compounds, the local EDL layers exhibit pronounced restructuring, featuring bending, breaking, and/or reconnecting patterns that switch when the size of the local interphase cluster changes. These EDL reconfiguration patterns are likely universal during nucleation and growth, calling into attention the hitherto hidden contribution of EDL heterogeneity on electrochemical processes.